Online Hemodiafiltration Inhibits Inflammation-Related Endothelial Dysfunction and Vascular Calcification of Uremic Patients Modulating miR-223 Expression in Plasma Extracellular Vesicles - Cavallari, Claudia; Dellepiane, Sergio; Fonsato, Valentina; Medica, Davide; Marengo, Marita; Migliori, Massimiliano; Quercia, Alessandro D; Pitino, Adriana; Formica, Marco; Panichi, Vincenzo; Maffei, Stefano; Biancone, Luigi; et al. (The Journal of immunology (1950), 2019)
Decreased inflammation and cardiovascular mortality are evident in patients with end-stage chronic kidney disease treated by online hemodiafiltration. Extracellular vesicles (EV) are mediators of cell-to-cell communication and contain different RNA types. This study investigated whether mixed online hemodiafiltration (mOL-HDF) beneficial effects associate with changes in the RNA content of plasma EV in chronic kidney disease patients. Thirty bicarbonate hemodialysis (BHD) patients were randomized 1:1 to continue BHD or switch to mOL-HDF. Concentration, size, and microRNA content of plasma EV were evaluated for 9 mo; we then studied EV effects on inflammation, angiogenesis, and apoptosis of endothelial cells (HUVEC) and on osteoblast mineralization of vascular smooth muscle cells (VSMC). mOL-HDF treatment reduced different inflammatory markers, including circulating CRP, IL-6, and NGAL. All hemodialysis patients showed higher plasma levels of endothelial-derived EV than healthy subjects, with no significant differences between BHD and mOL-HDF. However, BHD-derived EV had an increased expression of the proatherogenic miR-223 with respect to healthy subjects or mOL-HDF. Compared with EV from healthy subjects, those from hemodialysis patients reduced angiogenesis and increased HUVEC apoptosis and VSMC calcification; however, all these detrimental effects were reduced with mOL-HDF with respect to BHD. Cell transfection with miR-223 mimic or antagomiR proved the role of this microRNA in EV-induced HUVEC and VSMC dysfunction. The switch from BHD to mOL-HDF significantly reduced systemic inflammation and miR-223 expression in plasma EV, thus improving HUVEC angiogenesis and reducing VSMC calcification.